Chapter 7 Finding the global in the local Constructing population in the search for disease genes - Sturdy, Steve (Social Histories of Medicine, 2020)
Numerous studies describe the genetic make-up of populations living outside Europe and North America. Many of these tackle human genetic variation with the explicit aim of identifying gene variants of medical significance for the populations studied. However, the chapter points to rather different motivations, showing how recent studies documenting the genetic constitution of non-Western populations have grown out of, and serve the purposes of, efforts to identify genetic factors which influence the health of populations in Europe and North America. Analysing the past thirty-five years of medical research literature, the chapter shows how, in this context, efforts to identify genetic variants of possible significance for disease aetiology have shifted to include large-scale association studies in populations rather than families. It discusses how research with local concerns must nonetheless take into account the global distribution of genes and genotypes, thus making studies of the genetic causes of disease, wherever conducted, increasingly global in their purview. The chapter also argues that this recent knowledge of human population genomics has developed in a way which reinscribes ideas of racial difference into biomedical understanding of human populations, and creates tools for excluding supposedly non-Western populations from research oriented towards the concerns of Western institutions.